Value Stream Mapping as a Method Enabling the Optimization of the Technological Process Based on the Example of the ZSP "Lubiana" S.A. Porcelain Tableware Company - Blicharska, Małgorzata; Szmaglik, Iwona; Murawski, Lech; Szeleziński, Adam; Jasiński, Krzysztof; Januszewski, Tadeusz (Scientific Journal of Gdynia Maritime University, 2025)
Value Stream Mapping (VSM) is a technique aimed at optimizing the manufacturing process by minimizing waste and other losses that affect the amount of value added. It is a graphical method that uses a block diagram to illustrate the key stages of the production process, pinpoint areas and causes of delays in receiving the final product, and provide numerical process data as indicators of efficiency and profitability at each production stage. This article presents the method of building a value stream map using the example of ZPS "Lubiana" S.A. and attempts to assess the effectiveness of this method.